2021
DOI: 10.1073/pnas.2102945118
|View full text |Cite
|
Sign up to set email alerts
|

Gender inequities in the online dissemination of scholars’ work

Abstract: Unbiased science dissemination has the potential to alleviate some of the known gender disparities in academia by exposing female scholars’ work to other scientists and the public. And yet, we lack comprehensive understanding of the relationship between gender and science dissemination online. Our large-scale analyses, encompassing half a million scholars, revealed that female scholars’ work is mentioned less frequently than male scholars’ work in all research areas. When exploring the characteristics associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…However, the same gender biases that emerge in traditional article metrics (like citation count; Larivière et al, 2013 ) also emerge for online visibility. For instance, male-identified scientists received more attention than female-identified scientists among the top 25% of online scholars, regardless of the research area and the proportion of female-identified scientists in the research area ( Vasarhelyi et al, 2021 ). Thus, androcentric biases occur overall in the dissemination of online scholarship because people pay more/less attention to research based on the authors’ characteristics (gender, race, university affiliation, e.g., Vasarhelyi et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the same gender biases that emerge in traditional article metrics (like citation count; Larivière et al, 2013 ) also emerge for online visibility. For instance, male-identified scientists received more attention than female-identified scientists among the top 25% of online scholars, regardless of the research area and the proportion of female-identified scientists in the research area ( Vasarhelyi et al, 2021 ). Thus, androcentric biases occur overall in the dissemination of online scholarship because people pay more/less attention to research based on the authors’ characteristics (gender, race, university affiliation, e.g., Vasarhelyi et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, male-identified scientists received more attention than female-identified scientists among the top 25% of online scholars, regardless of the research area and the proportion of female-identified scientists in the research area ( Vasarhelyi et al, 2021 ). Thus, androcentric biases occur overall in the dissemination of online scholarship because people pay more/less attention to research based on the authors’ characteristics (gender, race, university affiliation, e.g., Vasarhelyi et al, 2021 ). But what we do not know is will research within psychology about sex/gender similarly be ignored or, perhaps, receive extra interest because it confirms or challenges the status quo .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that women's scientific work is less cited and gets less visibility on social media than men's (70). Social media is an important space for gaining credibility, visibility, and success, therefore, relevant to strengthen the presence of women in science.…”
Section: Menstrual Blood Cells Research On Twitter: Potentially Inter...mentioning
confidence: 99%
“…To the extent that diverse voices are included in the feedback process, the quality of the work also improves (Woolley et al, 2010). In academia, women's work continues to be underrepresented and undervalued (Knobloch-Westerwick et al, 2013;Vásárhelyi et al, 2021).…”
mentioning
confidence: 99%
“…Gendered power differentials also impact academic spaces in which women are underrepresented, paid less, and their work is valued less (Gruber et al, 2021;Kaatz & Carnes, 2014;Knobloch-Westerwick et al, 2013;Llorens et al, 2021;Schroeder et al, 2013;Vásárhelyi et al, 2021). These gendered power differences can be seen behaviorally in departmental seminar and conference Q&A sessions where, relative to women, men participate more (Carter et al, 2018;Hinsley et al, 2017;Käfer et al, 2018;Pritchard et al, 2014;Schmidt & Davenport, 2017;Telis et al, 2019).…”
mentioning
confidence: 99%